EFFECT OF VITAMIN D ADMINISTRATION ON VASCULAR ENDOTHELIAL GROWTH FACTOR EXPRESSION AND ANGIOGENESIS NUMBER IN ORTHODONTIC TOOTH MOVEMENT OF PREGNANT WISTAR RAT - Nareswari, Raden Ajeng Anindya Ratri; Narmada, Ida Bagus; Djaharu'ddin, Irwadi; Rahmawati, Dwi; Putranti, Nurul Aisyah Rizky; Nugraha, Alexander Patera (Journal of Postgraduate Medical Institute, 2019)
Objective: To analyze the effect of vitamin D administration on vascular endothelial growth factor (VGEF) expression and angiogenesis number during orthodontic tooth movement (OTM) in pregnant Wistar rats (Rattus norvegicus). Methodology: This was an experimental study with post-test only control group design. Lameshow's sample size formula was used with random sampling method. Twenty eight female Wistar rats were divided into 2 control groups (C+7 and C+14) and 2 experimental groups (E+7 and E+14). Their pregnancy was synchronized, 30g/mm force closed coil spring was given between their incisors and 1st left maxillary molar. Vitamin D (0.2mg/kg) was given every 3 days to E+7 and E+14. Maxillary bone of all groups was extracted. Angiogenesis number was examined by means of Hematoxylin Eosin staining while VEGF expression was examined with Immunohistochemistry staining. Mann-Whitney and analysis of variance with Tukey HSD post-hoc test (p <0.05) was performed based on Levene's test and Kolmogorov-Smirnov test result (p >0.05). Results: The lowest angiogenesis number was found in C+7 (11.11 ±5.95) and the highest was found in E+14 (23.83 ±7.10). Significant difference was obtained between C+7 and E+14 (p =0.003, p <0.05); E+7 and E+14 (p =0.013, p <0.05). The lowest VEGF expression was found in E+14 (3.09 ±1.14) while the highest was found in C+14 (6.26 ±2.39). There was no significant difference between each group (p >0.05). Conclusion: Vitamin D administration did not significantly increase VEGF expression and angiogenesis number in OTM of pregnant rats.